STUDENTS’ PERCEPTIONS ON THE UTILIZATION OF CHATGPT AND GOOGLE TRANSLATE IN ENGLISH LANGUAGE LEARNING - Rifhani Handayani L; Hardiyanti Hatibu (Journal of Innovation Research and Knowledge, 2024)
The rapid advancement of technology and the adoption of tools like Google Translate and ChatGPT have significantly transformed English language learning. This research examines the perspectives of first-semester students in the Primary School Teacher Education Program at Universitas Negeri Makassar regarding the use of these tools in their learning process.This study used a descriptive qualitative method to analyze the perceptions of students on the use of ChatGPT and Google Translate in English language learning. it enables researchers to collect and analyze data that can be extended to a larger population. Fifty students participated in semi-structured interviews and questionnaires to gather data using a descriptive qualitative approach. In conlusion, the findings show that there are 75% of students who prefer Google Translate for word and phrase translation than chatgpt, because of its ease of use and quickness. However, despite its outstanding features of ChatGPT, it is not quite attractive due to its complexity. This study identifies the elements that impact students' decisions, including effectiveness, familiarity, and convenience of use, and recommends combining the two technologies to maximize their potential to improve language learning results. This research highlights the factors influencing students' choices, such as ease of use, familiarity, and effectiveness, and suggests integrating both tools to optimize their potential in enhancing language learning outcomes